Informational Lobbying and Political Contributions - Morten Bennedsen; Sven E. Feldmann (Copenhagen Business School (CBS), Department of Economics, 2000)
Interest groups can influence political decisions in two distinct ways: by offering contributions to political actors and by providing them with relevant information that is favorable for the group. We analyze the conditions under which interest groups are more inclined to use one or the other channel of influence. First, we identify an indirect cost of searching for information in the form of an information externality that increases the cost of offering contributions. We then show that an extreme interest group might find it beneficial to abandon information provision altogether and instead seek influence solely via contributions. Finally, we apply our model to cast doubt on the "conventional wisdom" that competition among information providers increases the amount of information provided: when the identified information externality is taken into account, wee show that competition decreases information search. Thus, our analysis lends support to a rather cynical view of lobbying wherein lobby groups provide little or no useful information to the political process.
hdl:10398/7608
Keywords: H89; 330; Informational lobbying; Political contributions; Information externalities